2007
DOI: 10.1002/jcd.20164
|View full text |Cite
|
Sign up to set email alerts
|

A non‐existence result on Cameron–Liebler line classes

Abstract: Cameron-Liebler line classes are sets of lines in PG(3, q) that contain a fixed number x of lines of every spread. Cameron and Liebler classified Cameron-Liebler line classes for x ∈ {0, 1, 2, q 2 − 1, q 2 , q 2 + 1} and conjectured that no others exist. This conjecture was disproven by Drudge for q = 3 [8] and his counterexample was generalised to a counterexample for any odd q by Bruen and Drudge [4]. A counterexample for q even was found by Govaerts and Penttila [9]. Non-existence results on Cameron-Liebler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Such a line must then have at least 1 + p ≥ 3 points of B and thus the line must be a line contained in the quadric. Using this observation, De Beule et al [9] could show that PG(3, q) does not have a Cameron-Liebler line class of parameter x with 2 < x < q/2. The bound x < q/2 results from the requirement that the corresponding blocking set has to be small.…”
Section: Cameron-liebler Line Classesmentioning
confidence: 99%
“…Such a line must then have at least 1 + p ≥ 3 points of B and thus the line must be a line contained in the quadric. Using this observation, De Beule et al [9] could show that PG(3, q) does not have a Cameron-Liebler line class of parameter x with 2 < x < q/2. The bound x < q/2 results from the requirement that the corresponding blocking set has to be small.…”
Section: Cameron-liebler Line Classesmentioning
confidence: 99%
“…We prove that F is the union of x pairwise disjoint subspaces PG(r, q). This is already known for Q + (5, q), see [8]. We rely on Theorem 2.2.…”
Section: Lemma 23 (Govaerts and Stormementioning
confidence: 90%
“…Recently, many results in finite geometry were obtained by applying characterization results on minihypers [8,17,18]. In this paper, using characterization results on certain minihypers, we present new results on tight sets in classical finite polar spaces and weighted m-covers, and on weighted m-ovoids of classical finite generalized quadrangles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Later on it was found that these line classes have many connections to other geometric and combinatorial objects, such as blocking sets of PG(2, q), projective two-intersection sets in PG (5, q), two-weight linear codes, and strongly regular graphs. In the last few years, Cameron-Liebler line classes have received considerable attention from researchers in both finite geometry and algebraic combinatorics; see, for example, [7,20,21,26,11,10]. In [6], the authors gave several equivalent conditions for a set of lines of PG (3, q) to be a Cameron-Liebler line class; Penttila [23] gave a few more of such characterizations.…”
Section: Introductionmentioning
confidence: 97%